2015
DOI: 10.1186/s12864-015-1314-x
|View full text |Cite
|
Sign up to set email alerts
|

High correlation between genotypes and phenotypes of environmental bacteria Comamonas testosteroni strains

Abstract: BackgroundMembers of Comamonas testosteroni are environmental microorganisms that are usually found in polluted environment samples. They utilize steroids and aromatic compounds but rarely sugars, and show resistance to multiple heavy metals and multiple drugs. However, comprehensive genomic analysis among the C. testosteroni strains is lacked.ResultsTo understand the genome bases of the features of C. testosteroni, we sequenced 10 strains of this species and analyzed them together with other related published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 67 publications
2
36
0
Order By: Relevance
“…However, exceptions to this trend are the genus Comamonas , in which all four species with sequenced genomes have the pathway, and the SAR86 cluster, in which all three strains with sequenced draft genomes have the pathway. Recently, genotypic analysis of 14 Comamonas testosteroni strains revealed that the testosterone/cholate degradation pathway is part of the core genome of this species ( 31 ). Unfortunately, most of these genomes were not available at the time of our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, exceptions to this trend are the genus Comamonas , in which all four species with sequenced genomes have the pathway, and the SAR86 cluster, in which all three strains with sequenced draft genomes have the pathway. Recently, genotypic analysis of 14 Comamonas testosteroni strains revealed that the testosterone/cholate degradation pathway is part of the core genome of this species ( 31 ). Unfortunately, most of these genomes were not available at the time of our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the Comamonas strains could only oxidize Sb(III) but not As(III) (114,119,124,125). Furthermore, Hydrogenophaga taeniospiralis IDSBO-1, isolated by Terry et al (115), was shown to possess the aioA gene and oxidized As(III), but not Sb(III), under aerobic conditions.…”
Section: Microbial Antimony Cyclementioning
confidence: 99%
“…testosteroni [49][50][51], S. xenophaga [52,53] and N. oligotropha [54,55] were identified. These bacteria would be the indigenous bacteria in irrigation water and then colonized in the nutrient solution, and would aid in the self-purification of the recirculating nutrient solution.…”
Section: Discussionmentioning
confidence: 99%